Synthesis of Disentangled Ultra-High Molecular Weight Polyethylene: Influence of Reaction Medium on Material Properties - Giuseppe Forte; Sara Ronca (International Journal of Polymer Science)
The polymerization of ethylene to Ultra-High Molecular Weight Polyethylene (UHMWPE) in certain reaction conditions allows synthesis of nascent powders with a considerably lower amount of entanglements: the material obtained is of great interest from both academic and industrial viewpoints. From an academic point of view, it is interesting to follow the evolution of the metastable melt state with the progressive entanglements formation. Industrially, it is valuable to have a solvent-free processing route for the production of high modulus, high strength tapes. Since the polymer synthesis is performed in the presence of a solvent, it is interesting to investigate the influence that the reaction medium can have on the catalyst activity, resultant molecular characteristics, and polymer morphology at the macroscopic as wells as microscopic level. In this paper, we present the effect that two typical polymerization solvents, toluene and heptane, and mixtures of them, have on the catalytic performance and on the polymer properties. The observations are that an unexpected increase of catalyst activity, accompanied by a significant improvement in mechanical properties, is found when using a carefully chosen mixture of solvents. A tentative explanation is given on the basis of the presented results.